Comprehensive Behavioral Treatment of Trichotillomania: A Treatment Development Study. (May 2016) - Falkenstein, Martha J.; Mouton-Odum, Suzanne; Mansueto, Charles S.; Golomb, Ruth Goldfinger; Haaga, David A. F.
This study aimed to concretize and pilot test comprehensive behavioral (ComB) treatment of trichotillomania (TTM), to facilitate rigorous testing of its efficacy. ComB provides a conceptualization to develop individualized treatment and choose interventions for managing distinct factors that maintain the individual's hair pulling. It has been used by clinicians for almost three decades, yet was not previously manualized or studied empirically. A manual was drafted and revised based on patient ( N = 16) and therapist feedback, an intervention choice study demonstrated therapists reliably selected model-consistent interventions, and a therapist adherence measure was developed and tested. Uncontrolled preliminary data showed ComB to be highly acceptable, and it led to reduced TTM symptom severity and impairment, with large effects. Quality of life and disability also improved, with effects maintained at follow-up. This study resulted in the development of a manual and measures to be used in a randomized controlled trial (RCT) of ComB for TTM.